Distribusi Perindukan Aedes Sp di Desa Tales Kecamatan Ngadiluwih Kabupaten Kediri - Hesti Riski Febry Sohpyana; Ngadino Ngadino; Narwati Narwati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Dengue fever is a disease caused by dengue virus through the bite of Aedes sp. The highest number of deaths from DHF attacks in January 2019 in Ngadiluwih Subdistrict in Tales Village is as many as two people. This study aims to determine the distribution of breeding Aedes sp in Tales Village, Ngadiluwih District, Kediri Regency in 2019. This research was a descriptive survey research with cross sectional approach. The population in this study were 2759 houses, with sample size of 97 houses. The data obtained were processed with spatial analysis to obtain a map of the distribution of Aedes sp. The results of a survey conducted in Tales Village Ngadiluwih District Kediri Regency, the House Index figure was 20.6%. Breeding places with the most characteristics were found in water reservoirs of 20 (95.2%) containers, made from 10 cement (47.6%) containers, dark colored 15 (71.4%) containers, with open conditions 21 (100%) containers, as well as found in houses 16 (76.29%) containers. Positive contained 20 house of Aedes sp larvae. The distribution of breeds in Tales Village was mostly distributed in Sentono Hamlet with 6 houses. Advised to do conduct mosquito breeding site elimination activities such as 3M plus; processing used goods, closing water reservoirs, draining water reservoirs, larvicidal activities, raising fish and preventing mosquito bites. Such activities must continue to be done to eradicate mosquito breeding. Keywords: House Index (HI); breed distribution; Aedes sp ABSTRAK Penyakit DBD adalah penyakit yang disebabkan oleh virus dengue melalui gigitan nyamuk Aedes sp. Jumlah kematian terbanyak dari serangan penyakit DBD pada bulan Januari 2019 di Kecamatan Ngadiluwih pada Desa Tales yaitu sebanyak dua orang. Penelitian ini bertujuan untuk mengetahui distribusi perindukan Aedes sp di Desa Tales Kecamatan Ngadiluwih Kabupaten Kediri Tahun 2019. Penelitian ini merupakan penelitian survei deskriptif dengan pendekatan cross sectional. Populasi dalam penelitan ini sebanyak 2759 rumah, dengan ukuran sampel sebanyak 97 rumah. Data yang diperoleh diolah dengan analisis spasial untuk memperoleh peta distribusi perindukan nyamuk Aedes sp. Hasil penelitian dari survei yang dilakukan di Desa Tales Kecamatan Ngadiluwih Kabupaten Kediri, angka House Index sebanyak 20,6%. Tempat perindukan dengan karakteristik paling banyak ditemukan di tempat penampungan air 20 (95,2%) kontainer, berbahan semen 10 (47,6%) kontainer, berwarna gelap 15 (71,4 %) kontainer, dengan kondisi terbuka 21 (100%) kontainer, serta ditemukan di dalam rumah 16 (76,29%) kontainer. Positif mengandung larva Aedes sp sebanyak 20 rumah. Distribusi perindukan di Desa Tales paling banyak tersebar di Dusun Sentono sebanyak 6 rumah. Disarankan untuk melakukan kegiatan pemberantasan sarang nyamuk seperti 3M plus; mengolah barang bekas, menutup tempat peampungan air, menguras temat penampungan air, kegiatan larvasida, memelihara ikan dan mencegah gigitan nyamuk. Kegiatan seperti demikian harus terus dilakukan untuk memberantas perindukan nyamuk. Kata kunci: House Index (HI); distribusi perindukan; Aedes sp